2012
DOI: 10.1039/c2em00004k
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and optimization of an online system for the simultaneous measurement of atmospheric water-soluble constituents in the gas and particle phases

Abstract: In this work we present the results of extensive characterization and optimization of the Ambient Ion Monitor-Ion Chromatograph (AIM-IC) system, an instrument developed by URG Corp. and Dionex Inc. for simultaneous hourly measurements of the water-soluble chemical composition of atmospheric fine particulate matter (PM(2.5)) and associated precursor gases. The sampling assembly of the AIM-IC consists of an inertial particle size-selection assembly, a parallel-plate wet denuder (PPWD) for the collection of solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 61 publications
1
77
0
Order By: Relevance
“…However, a few issues arose during the first two years of operation, mainly related to saturation in the column during PM pollution episodes. It has also been shown that with the use of a concentrator in the AIM analyzer, reported ambient concentrations could be biased low by 9-26%, depending on the species (Markovic et al 2012). For these reasons, a 340 ml sample loop was installed on both anion and cation systems and used for this comparison.…”
Section: Ic Measurementsmentioning
confidence: 99%
“…However, a few issues arose during the first two years of operation, mainly related to saturation in the column during PM pollution episodes. It has also been shown that with the use of a concentrator in the AIM analyzer, reported ambient concentrations could be biased low by 9-26%, depending on the species (Markovic et al 2012). For these reasons, a 340 ml sample loop was installed on both anion and cation systems and used for this comparison.…”
Section: Ic Measurementsmentioning
confidence: 99%
“…A detailed description of this inlet design and the performance characteristics of the AIM-IC system can be found in Markovic et al [2012]. Briefly, particle size selection was carried out using a 2.5 micron particulate matter (PM 2.5 ) inertial impactor (URG Corp., Chapel Hill, NC) on a 3 L min À1 sample flow.…”
Section: Hono Particulate Nitrite and Supporting Measurementsmentioning
confidence: 99%
“…The inlet was overflowed with this gas combination for more than 8 h. NH 3(g) and HONO (g) were produced from a permeation device housed in a temperature-controlled oven [e.g., Markovic et al, 2012], with HONO (g) being generated at 50% relative humidity in a NaNO 2(s) -packed tubing fed with HCl (g) from a permeation device according to the method of Febo et al [1995]. A maximum breakthrough of 4% of gas phase HONO (g) to the particle channel was observed at the highest examined HONO (g) mixing ratio of 2 ppbv, which is above the maximum HONO (g) observed in this study.…”
Section: Aim-ic Hono Collection Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques do not involve sampling on filters and are thus free from the above sampling artifacts. To name some, the steam-jet aerosol collector (SJAC; Khlystov et al 1995), the aerosol mass spectrometer (AMS; Jayne et al 2000;Allan et al 2003), the flash volatilization nitrate monitor (R&P8400N; Stolzenburg and Hering 2000), the ambient ion monitor-ion chromatograph (AIM-IC; Markovic et al 2012), and the particle-into-liquid sampler coupled with ion chromatograph (PILS-IC; Weber et al 2001).…”
Section: Introductionmentioning
confidence: 99%